The Effect Of Work Stress and Emotional Intelligence On Job Satisfaction And Its Impact On The Performance Of Nurses At Palembang Bari Regional General Hospital - Desiana; Djatmiko Noviantoro; Nashir; Sari Sakarina (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
A hospital is an integral part of a health and social organisation with various functions, particularly in providing services, preventing, and treating diseases in the community. Nurses, as "the caring profession," play a crucial role in providing quality healthcare services in hospitals. Nurses are the most important human resource in hospitals due to their dominant number (55-65%), therefore, attention is needed to ensure nurse performance in carrying out their duties and functions in healthcare services to patients. A nurse's ability to manage emotions will determine the level of stress a nurse feels, which will then affect job satisfaction and ultimately affect their performance. The purpose of this study was to determine the effect of work stress and emotional intelligence on job satisfaction and its impact on nurse performance at Palembang BARI Regional Hospital. This study used a Structural Equation Model (SEM) operated through the Partial Least Square (PSL) programme. The sampling technique in this study employed stratified random sampling with 73 samples. The results of the hypothesis test showed that job stress affects nurse job satisfaction at Palembang BARI Regional Hospital with a statistical t value of 3.744 > 1.96 or P Value 0.000 < 0.05. Emotional intelligence affects job satisfaction with a statistical t value of 5.276 > 1.96 or P Value 0.000 < 0.05. Job stress affects nurse performance with a statistical t value of 4.443> 1.96 or P Value 0.000 <0.05. Emotional intelligence influences performance with a t statistic of 3.286 > 1.96 or a P Value of 0.001 < 0.05. Job satisfaction influences nurse performance with a t statistic of 5.409 > 1.96 or a P Value of 0.000 < 0.05. The results of this study have implications for managerial policies that can be used as a reference by management in determining the priority scale of what policies should be implemented.